The Needs of School Professionals for Eating Disorder Prevention in Australian Schools: A Mixed-Methods Survey - Kirrilly M. Pursey; Melissa Hart; Alexis Hure; Hei Man Cheung; Liting Ong; Tracy L. Burrows; Zali Yager (MDPI AG, 2022)
(1) Background: School professionals such as teachers and counsellors are uniquely positioned to facilitate discussion around disordered eating and body image; however, little is known about the needs of school professionals with respect to eating disorder prevention. This study aimed to explore the needs and perceptions of Australian school professionals regarding eating disorder prevention. (2) Methods: School professionals were recruited to a mixed-methods online cross-sectional survey. The survey assessed demographics and perceived needs and attitudes to eating disorder prevention. (3) Results: Most participants (92%) were willing to participate in eating disorder prevention; however, only 61% reported good knowledge and 41% reported feeling confident in implementing eating disorder prevention. Those who had received training in eating disorders (24%) reported higher confidence (p = 0.02) and knowledge (p = 0.04). Only 66% of respondents reported that all teachers should be involved in eating disorder prevention while barriers including workload, knowledge, and resources were commonly highlighted. Fewer respondents working in primary school settings reported the need for prevention approaches (p = 0.046). (4) Conclusions: Despite a willingness to be involved in the prevention of eating disorders, there are inconsistencies in attitudes regarding the role of school professionals in eating disorder prevention. The findings of this study reinforce that understanding professional roles, school settings, and personal attitudes is critical in the development of more efficacious school professional training and prevention interventions.